Efficacy and safety of PARP inhibitors in patients with BRCA-mutated advanced breast cancer: A meta-analysis and systematic review. (December 2021) - Sun, Ximu; Wang, Xin; Zhang, Jie; Zhao, Zhixia; Feng, Xin; Liu, Lihong; Ma, Zhuo
Abstract: Objective: This meta-analysis aimed to investigate the efficacy and safety of poly (adenosine diphosphate-ribose) polymerase (PARP) inhibitors in BRCA- mutated advanced breast cancer patients comprehensively. Methods: We conducted a systematic literature research through PubMed, the Cochrane Central Register of Controlled Trials (CENTRAL), Embase, China National Knowledge Infrastructure (CNKI), wanfang, China Biology Medicine disc (CBMdisc), and ClinicalTrials.gov from inception to January 2021. Randomized controlled trials (RCTs) with available data comparing PARP inhibitors versus control therapy in BRCA -mutated advanced breast cancer were eligible for analysis. Statistical analyses were performed with Review Manager (RevMan) version 5.4 and R version 4.0.3. Results: 1706 studies were retrieved in total, and 4 RCTs with 1540 patients were eligible for meta-analysis finally. The results showed that progression-free survival (PFS) and overall survival (OS) were significantly improved in germline BRCA -mutated breast cancer patients with PARP inhibitors (HR 0.64, 95% CI [0.56–0.74]; HR 0.86, 95% CI [0.74–0.99], respectively) with no significant heterogeneity across studies (I 2 = 22%, χ 2 p = 0.28; I 2 = 0%, χ 2 p = 0.70, respectively). There was no significant difference in the overall adverse events (AEs), grade≥3 AEs and AEs leading to treatment discontinuation between PARP inhibitor arms and control arms (RR 1.01, 95% CI [0.99–1.02]; RR 0.95, 95% CI [0.83–1.09]; RR 1.17, 95% CI [0.87–1.57], respectively). Based on the available data, PARP inhibitors provided comparable or better results than control arms in improving the quality of life in BRCA -mutated advanced breast cancer patients. Conclusions: PARP inhibitors prolonged PFS and OS among patients with BRCA -mutated advanced breast cancer with tolerable safety and improved quality of life. Graphical abstract: Image 1 Highlights: PARP inhibitors showed encouraging efficacy in BRCA-mutated advanced breast cancer. The safety of PARP inhibitors was tolerable. We included both PARP inhibitor monotherapy and combination therapy studies.